Da aldeia à favela: estudo da identidade de índios Pankararu no Real Parque - França, Vanessa Abdo (2008)
In spite of the fact that this study focuses on an indian population originally from Permambuco, the background of this research is the city of São Paulo and its idiosincries as an urban, metropolitan region with its serious social inequalities. Our objective was to conduct a study about the identity of the Pankararu Indians residing in the Real Parque Favela in the city of São Paulo. In order to do this, interview data was analyzed in a qualitative manner, with the supposition that the interviewees are carriers of a social discourse. The data was done within a social psychological framework. In the study one can see that for the interviewees, the notion of Pankararu Indian is defined by descendence from a location that attributes the condition of being Indian and not the phenotypical characteristics. In relation to the non-indian residents of the favela, there is at the same time a recognition of being a member of the favela while feeling a certain distance from that situation and a total identification with their ethnic origins. The identification with the situation of residing in the favela is primarily related to the problems they confront. In this way, Indian identity is important in order to go against the naturalization of poverty principally because the condition of being a resident of the favela is a trap that may deconstruct the identity of the Pankaraus